Odpowiedzi

2010-03-28T11:08:36+02:00
3x+4=2x+7
3x-2x=7-4
x=3

12-x=3x-4
x-3x=-4+12
-2x=8/:2
x=4

6x-1=3x+5
6x-3x=5+1
3x=6/:3
x=2

x-3=6x+12
x-6x=12+3
5x=15/:5
x=3

5(x-5)=x-9
5x-25=x-9
5x-x=-9+25
4x=16/:4
x=4

2x+1=7-x
2x+x=7-1
3x=8/:3
x=3/8 (ułamek)

2x+2=5x-10
2x-5x=-10-2
-3x=12/:3
x=4

20-3x=2x+5
-3x-2x=5-20
-5x=15/:5
x=3

7x-3x=21-x
7x-3x+x=21
5x=21/:5
x=21/5(ułamek)

3(x-2)-7=8
3x-6-7=8
3x=8+6+7
3x=20/:3
x=20/3(ułamek)
1 5 1
Najlepsza Odpowiedź!
2010-03-28T11:26:26+02:00

a)3x+4=2x+7
3x-2x=-4+7
x=3
b)12-x=3x-4
-x-3x=-12-4
-4x=-16/:(-4)
x=4
c)6x-1=3x+5
6x-3x=1+5
3x=6/:3
x=2
d)x-3=6x+12
x-6x=3+12
-5x=15/:(-5)
x=5
e)5(x-5)=x-9
5x-25=x-9
5x-x=25-9
4x=16/:4
x=4
F)2x+1=7-x
2x+x=-1+7
3x=6/:3
x=2
g)2x+2=5x-10
2x-5x=-2-10
-3x=-12/:(-3)
x=4
h)20-3x=2x+5
-3x-2x=-20+5
-1x=-15/:(-1)
x=15
i)7x-3x=21-x
7x-3x+x=21
5x=21/:5
x=4,2
j)3(x-2)-7=8
3x-6-7=8
3x=6+7+8
3x=21/:3
x=7
2010-03-28T11:27:34+02:00
3x+4=2x+7 /-2x
x+4=7 /-4
x=3


12-x=3x-4 /+x
12=4x-4 /+4
16=4x /:4
4=x


6x-1=3x+5 /+1
6x=3x+6 /-3x
3x=6 /:3
x=2


x-3=6x+12 /-12
x-15=6x /-x
-15=5x /:5
-3=x


5(x-5)=x-9
5x-25=x-9 /-x
4x-25=-9 /+25
4x=16 /:4
x=4


2x+1=7-x /+x
3x+1=7 /-1
3x=6 /:3
x=2


2x+2=5x-10 /-2x
2=3x-10 /+10
12=3x /:3
4=x


20-3x=2x+5 /+3x
20=5x+5 /-5
15=5x /:5
3=x


7x-3x=21-x
4x=21-x /+x
5x=21 /:5
x=5,2

3(x-2)-7=8
3x-6-7=8 /+6
3x-7=14 /+7
3x=21 /:3
x=7